Thiopurines exert harmful effects on spermatogenesis in Nudt15R138C knock-in mice - Yokota, Yoshihiro; Imai, Takayuki; Kawahara, Masahiro; Inatomi, Osamu; Nishida, Atsushi; Kakuta, Yoichi; Masamune, Atsushi; Andoh, Akira (Journal of gastroenterology, 2024)
Background The association between thiopurine use and testicular reproductive functions remains unclear. In this study, we investigated whether thiopurines affect testicular functions based on the NUDT15 genotypes using Nudt15 R138C knock-in mice. Methods The male Nudt15 R138C knock-in mice (9–12 weeks) were treated with mercaptopurine (MP: 0.5 mg/kg/day) for 4 or 12 weeks. To examine reversibility, some mice were maintained for a further 12 weeks under MP-free condition. Results After MP treatment for 4 weeks, Nudt15 R138C/R138C mice exhibited a significant reduction of testis weight compared to Nudt15 + / + mice and Nudt15 + / R138C mice. The epithelial height and diameter of seminiferous tubules were significantly reduced in Nudt15 R138C/R138C mice compared to Nudt15 + / + and Nudt15 + / R138C mice. Apoptotic cells were significantly increased in Nudt15 R138C/R138C mice, and most of apoptotic cells were spermatogonia. There were no significant changes in sperm counts and sperm morphology in MP-treated Nudt15 R138C/R138C mice after 4-week MP treatment. On the other hand, after MP treatment for 12 weeks, the Nudt15 + / R138C mice, but not Nudt15 + / + mice, exhibited a significant reduction in the testis weight and atrophic changes of seminiferous tubules, but these changes disappeared after 12-week rearing under MP-free condition. Despite a significant increase in abnormal sperm rate, there were no changes in the ability to conceive. No differences in serum levels of follicle-stimulating hormone or testosterone were observed between MP-treated Nudt15 +/ R138C and Nudt15 + / + mice after 12-week MP treatment. Conclusions Thiopurines exert harmful effects on testicular reproductive function according to host NUDT15 genotypes.